MANAGING THE PROBLEMS OF ARTISANAL AND SMALL-SCALE GOLD MINING AT SEKOTONG AREA, WEST LOMBOK - BAMBANG YUNIANTO (Indonesian Mining Journal, 2012)
Artisanal and small-scale mining of gold at Sekotong area, West Lombok is conducted illegally. This gold mining is one of the examples of the mining in this country that retains the issue root of social, economic and cultural community. This paper tries to assess the issue and its solution based on the survey result of the current issues team from the R&D Centre of Mineral and Coal Technology. Based on the assessment relating to the policy of regional spatial plan, the gold potential in the area should be allocated partly for the artisanal and small-scale mining (WPR) in accordance with Law Number 4 Year 2009. In the earlier growth, the mining needs guidance, education and training in either capital aspect, business or mining technique. That is why, the role of the regional government is absolutely required.